Cost-benefit analysis of industrial and homemade dendrometer bands Análise do custo-benefício de dendrômetros industriais e artesanais - Fabrício Alvim Carvalho; Jeanine Maria Felfili (Acta Botânica Brasílica, 2011)
Dendrometer bands are used to make repeated measurements of tree radial growth. Two types of dendrometers are used worldwide, the industrial and the homemade. Homemade dendrometers prevail in Brazilian forestry studies, but researchers have trouble constructing and installing them. An easier solution is to use industrial dendrometer bands, but they are not produced in Brazil and, therefore, are expensive and might not be appropriate for local environmental conditions. We analyzed trunk growth measurements each month (from February 2008 to January 2009) using both industrial (imported) and homemade (national components) dendrometer bands installed on 20 trees of Acacia tenuifolia in a seasonally dry forest on limestone outcrops in central Brazil. Cost-benefit comparative analysis of measurements and prices indicates that homemade dendrometer bands have all benefits, and none of the problems, of the imported industrial dendrometer bands, such as the following: (1) similar precision of measurements (correlation analysis: r > 0.930, P < 0.01; permutation t-test: P > 0.55), (2) much lower costs (10 to 15 times cheaper), (3) easily manipulated and installated in the field, and (4) absence of some damage to tree trunks that are caused by industrial dendrometers. Os dendrômetros são utilizados para realizar medidas repetidas de crescimento radial arbóreo. Dois tipos de dendrômetros são mundialmente utilizados, o industrial e o artesanal. Os dendrômetros artesanais predominam nos estudos florestais no Brasil, mas os pesquisadores têm o trabalho de construí-los e instalá-los. Uma solução mais fácil é o uso de dendrômetros industriais, mas eles não são produzidos no Brasil e, portanto, são mais caros e podem não ser adequados às condições ambientais locais. Foram analisadas as medidas pareadas mensais de crescimento do tronco (de fevereiro de 2008 a janeiro de 2009) de dendrômetros industriais (importados) e artesanais (feitos com componentes nacionais), instalados em 20 árvores de Acacia tenuifolia numa floresta estacional decidual sobre afloramentos calcários no Brasil Central. A análise de custo-benefício entre das medidas e dos preços dos dois instrumentos indicou que os dendrômetros artesanais possuem todos os benefícios e nenhum dos problemas dos industriais importados: (1) precisão semelhante nas medidas (análise de correlação: r > 0,930, P < 0,01; teste t permutado: P > 0,55), (2) custos bem menores (10 a 15 vezes mais baratos), (3) facilidade na manipulação e instalação no campo, e (4) ausência de alguns danos nos troncos que foram provocados pelos dendrômetros industriais.